Ethical Conflicts between Patient Autonomy and Physician Centered Paternalism: An Account of Justified Paternalism - Tarafdar, Abhijit (Asian Journal of Philosophy and Religion, 2025)
This paper critically analyzes the ethical tension between patient autonomy and physician based paternalism within the doctor–patient relationship. The core problem lies in the asymmetry of medical knowledge, which has long been used as a tool to justify paternalistic interventions by physicians. Paternalistic interference breeds many moral questions from the perspective of patient autonomy and liberty and it inevitably creates ethical issues in doctor- patient relationship in the past few decades. With the advent of medical technology and awareness of patient autonomy, liberty, patients’ right, many critics have started to inveigh against the domination of physicians and give emphasize on patient autonomy bestowing all the responsibilities upon the patients in medical setting. There is also another view regarding the authority of medical decision making which tries to combine the part of liberty or patient autonomy with a soft or lesser degree of physician centered paternalism. This paper explores this ethical conflict and defends a model of limited medical paternalism that supports rather than undermines patient autonomy, demonstrating their potential compatibility in modern healthcare.